ChemInform Abstract: Lyngbouilloside and Related Macrolides from Marine Cyanobacteria. Issue 49 (3rd December 2013) - El Marrouni, Abdelatif; Kolleth, Amandine; Lebeuf, Raphael; Gebauer, Julian; Prevost, Sebastien; Heras, Montserrat; Arseniyadis, Stellios; Cossy, Janine
Abstract Review: strategies to synthesize these natural products; 72 refs.